The making and breaking of SAS-6: structural insights and inhibitor search for n-terminal domain dimerisation - Busch, J (2017)
SAS-6 is the structural core of the forming centriole - a cylindrical protein complex, which is an essential component of the centrosome. Oligomerisation of SAS-6 is crucial for successful centriole duplication and is achieved through two dimerisation domains in the SAS-6 protein; a long C-terminal coiled-coil domain and a globular N-terminal dimerisation domain. As core components of the centrosome, centrioles help facilitate various cellular functions. They are involved in the anchoring of flagella and cilia to the membrane and in coordinating the spindle apparatus during chromosome segregation. A deeper insight into the molecular mechanisms at play in the centriole duplication process would have implications on our understanding of fundamental cell division processes and a number of related diseases. Here the involvement of an unstudied loop region in the C. elegans SAS-6 N-terminal domain dimerisation is described. Combining structural biology, biophysical and computational techniques, the molecular interactions of this loop were explored, contributing to the oligomerisation of SAS-6 at the N-terminal dimer interface. Furthermore, the screening and testing of small molecule inhibitors of the SAS-6 N-terminal domain dimerisation is described, targeting a hydrophobic pocket in the domain. Two candidate compounds are presented as a result of the screens and next steps towards structure based compound design are suggested, based on computational analysis. The search for inhibitory compounds includes a set-up of an in-house virtual screening pipeline, as well as in vitro screening efforts and a new crystallographic structure of the H. sapiens SAS-6 N-terminal domain. By investigating the making and breaking of the SAS-6 N-terminal domain dimerisation, light is shed on so far neglected details of this essential protein-protein interaction and advancements towards a SAS-6 oligomerisation inhibitor described, which could ultimately be used for new approaches in cell cycle research and might open up new avenues for medical research by binding a disease relevant target.